Проблемно-тематическое своеобразие поэзии Константина Ефетова - Яблоновская, Н.В. (Культура народов Причерноморья, 2013)
В статье рассматривается проблемно-тематическое своеобразие поэзии современного
крымского поэта, ученого-биолога, профессора Константина Ефетова. Своеобразие афористиший К.
Ефетова (термин предложен самим поэтом) автор статьи усматривает в свободном от
назидательности философско-моралистическом содержании стихотворений, заключенных в
афористическую форму; многомерности, неоднозначности, а иногда и парадоксальности авторских
выводов и оценок; ироничности поэтической интонации. У статті розглядається проблемно-тематична своєрідність поезії сучасного кримського
поета, вченого-біолога, професора Костянтина Єфєтова. Своєрідність афоривіршів К. Єфєтова
(термін запропонований самим поетом) автор статті вбачає у вільному від повчальності філософсько-
моралістичному змісті віршів, уміщених в афористичну форму; багатомірності, неоднозначності, а
інколи й парадоксальності авторських висновків і оцінок; іронічності поетичної інтонації. The article deals with the topical originality of the poetry of modern Crimean poet, scholar and
biologist Professor Konstantin Efetov. The author notes the dual nature of the K. Efetov’s poems-paradoxes
("aphoripoems," as they are called by the poet himself), which are combined the traditional views and attitudes,
on the one hand, and on the other hand – a devastating debunking them. Capacious antinomic form corresponds
to the content of the poems – philosophical, ambiguous, multifaceted. The main themes of K. Efetov’s poetry –
the meaning of life, the friendship, the love, and the battle of the sexes, the man and the humanity, the man and
the time, the man and the society, the man and the nature. The feature of most aforipoems is the amazing ability
of the poet to see the absurdity in the traditional, the new in the old, the abnormal in the normal. The author sees
the originality of the K. Efetov’s aphoripoems in the philosophical and the moralistic content which is free of
didacticism; in aphoristic form of the poem; in the multi-dimensional, ambiguous, and sometimes paradoxical
conclusions and evaluation; in the ironic poetic tone.